Involving hard-to-reach ethnic minorities in low-budget health research: lessons from a health survey among Moluccans in the Netherlands. (December 2016) - Bodewes, Adee; Kunst, Anton
Abstract Background There is little evidence on which strategies are effective in recruiting minority groups in low-budget health surveys. We evaluated different recruitment strategies for their impact on response rates in a hard-to-reach minority population in the Netherlands. Methods We conducted a health survey in 19 Moluccan districts (MDs). Each MD had its own set of recruitment strategies, such as information meetings, involving social or local media, involving community organizations, and door-to-door collection. The association between recruitment strategies and MD-specific response rates was assessed with logistic regression analysis. Results The overall response rate was 24 %, and varied from 9 to 58 %. Higher rates were obtained when the strategy included door-to-door collection (OR 1.57) and 'active' key informants (OR 1.68). No positive associations with response rates were observed of the other strategies. Conclusions The overall low response rate in this study may be due to high levels of distrust, segmentation within the community and high respect for privacy among Moluccans. Our study shows that in such communities, response may be increased by a highly personal recruitment approach and a strong commitment and participation of community key-figures.